Understanding the Digital Literacy Skills of Digital Natives: A Case Study of LIS Undergraduates in a Nigerian University - Dr. Iguehi Joy Ikenwe; Dr. Afebuameh James Aiyebelehin; Osarumwense Adjarho (International Journal on Integrated Education, 2022)
Understanding the digital literacy skills of undergraduates is key to serving them in the 21st century university library. In view of this, this study investigated the digital literacy skills of LIS undergraduates in a Nigerian University. The descriptive survey design was adopted. The population of the study comprised 269 LIS undergraduates in Ambrose Alli University, Ekpoma. Total enumeration sampling technique was used since the population was manageable. The questionnaire was used to gather data. The data gathered was analyzed with percentages and mean. The findings showed that: the students’ ability to locate digital content was high (x ̅=2.74); the students’ ability to create digital contents was high (x ̅=2.59); and the students’ ability to communicate digital contents was equally high (x ̅=2.79).Furthermore, the findings revealed that the majority of the students acquired their digital competencies through social media (48.1%) and Online classes (37%). The implication of these findings is that since the students have considerable digital literacy skills, faculty and librarians who deal with the students must expose the students to digital learning by using online platforms for teaching, learning, and information dissemination.